Analisis Manajemen Reputasi Online Telkomsel Terkait Keluhan Pelanggan Pada Platform Digital - Habibatul Wa’dah; Indah Meilina; Safira Dwinawati Safitri; Tria Patrianti (Peneliti.net, 2023)
The rapid development of technology has had an impact on the telecommunications world. With the creation of cell phones that make it easier for people to shorten distances and time, indirectly opening new business opportunities and competition, namely cellular operators (providers). This study aims to explain Telkomsel's online reputation management analysis regarding customer complaints on digital platforms. The results of this study indicate that Telkomsel has good online reputation management in dealing with customer complaints on digital platforms, as evidenced by Telkomsel continuing to provide good service and responsiveness in dealing with customer complaints about the obstacles they experience through the mytelkomsel application and digital platforms owned by Telkomsel or can even go directly to the nearest Grapari.